Geographic disparities in cardiovascular mortality among patients with myelodysplastic syndromes: A population-based analysis. (October 2022) - Adrianzen-Herrera, Diego; Sparks, Andrew D.; Shastri, Aditi; Zakai, Neil A.; Littenberg, Benjamin
Abstract: Introduction: Clonal hematopoiesis, a precursor to myelodysplastic syndromes (MDS), constitutes a novel cardiovascular disease (CVD) risk factor, causing growing interest in cardiovascular outcomes in MDS. Rurality is associated with increased CVD but studies on cardiovascular geographic disparities in MDS are lacking. Methods: Using the U.S. Surveillance, Epidemiology, and End Results (SEER) registry, we identified 52, 750 MDS patients between 2001 and 2016. Rurality was defined using Rural-Urban Continuum Codes. Cox regression estimated the association of rurality and cardiovascular death. Results: MDS incidence was equal in urban and rural populations (6.7 per 100, 000). Crude probability of cardiovascular death was higher among rural MDS patients. Adjusting for age, sex, race/ethnicity, marital status, insurance, and MDS risk (defined from histology), rural patients had 12% increased risk of CVD death compared to urban patients (HR=1.12, 95%CI 1.03–1.21). HR for CVD death was 1.22 (95%CI 1.01–1.5) in patients from the most rural areas (less than 2500 urban population). Among MDS patients younger than 65 years, rurality was associated with 25% increased risk of CVD death (HR=1.25, 95%CI 1.01–1.59). Discussion: This population-based analysis suggests that rural residence is linked to higher burden of cardiovascular death in patients with MDS. The disparity is not explained by demographic factors or MDS risk. Interventions targeting CVD may improve outcomes in rural MDS patients. Highlights: Rural MDS patients had 12% increased risk of cardiovascular mortality compared to urban patients. Demographic factors and MDS risk did not explain the rural/urban difference in cardiovascular death. The rural to urban disparity in cardiovascular death was larger in MDS patients younger than 65.